2013
DOI: 10.5455/pmb.1-1345816200
|View full text |Cite
|
Sign up to set email alerts
|

Medical Error Types and Causes Made by Nurses in Turkey

Abstract: AIM: This study was carried out as a descriptive study in order to determine types, causes and prevalence of medical errors made by nurses in Turkey. METHOD: Seventy eight (78) nurses who have worked in a randomly selected hospital from five hospitals in Giresun city centre were enrolled in the study. The data was collected by the researchers using the ‘Information Form for Nurses’ and ‘Medical Error Form’. The Medical Error Form consists of 2 parts and 40 items including types and caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 20 publications
0
22
0
4
Order By: Relevance
“…Accordingly, nurses play a significant role in preventing malpractice. However, this does not necessarily mean that nurses do not make errors; many medical errors are also known to be committed by nurses, and these errors may risk the health of patients (ICN , Alemdar & Aktaş , Kılıç & Elbaş Özhan ). Thus, this study is important because it determined the conditions surrounding nurses' medical errors as well as the frequency of medical errors and their reasons; consequently, this study's results can contribute to the prevention of or reduction in medical errors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, nurses play a significant role in preventing malpractice. However, this does not necessarily mean that nurses do not make errors; many medical errors are also known to be committed by nurses, and these errors may risk the health of patients (ICN , Alemdar & Aktaş , Kılıç & Elbaş Özhan ). Thus, this study is important because it determined the conditions surrounding nurses' medical errors as well as the frequency of medical errors and their reasons; consequently, this study's results can contribute to the prevention of or reduction in medical errors.…”
Section: Discussionmentioning
confidence: 99%
“…, Kapucu ), excessive workload, excessive number of monthly night shifts, stress, tasks outside of nursing (Özata & Altunkan , Cebeci et al . , Alemdar & Aktaş ), lack of communication within the healthcare team (Gökdoğan & Yorgun , Petrova ), lack of knowledge, occupational inexperience, carelessness, negligence (Ertem et al . ), difficult working conditions such as working with critically ill patients, intensive work stress, inadequate working conditions and shift working (Garetson , Petrova , Zencirci , Özata et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hastanelerde en çok yapılan tıbbi hata türlerinin başında; ilaç hataları, hastane enfeksiyonları, yatak yaraları, tedavide gecikme veya tedavi yapmama, tanı koymada gerçekleşen hatalar ve ameliyat komplikasyonları gelmektedir (6,(23)(24)(25). Öğrenciler, hasta güvenliği denildiğinde; ilaç güvenliğinin sağlanması, hastane enfeksiyonlarının önlenmesi ve hasta düşmelerinin önlenmesi şeklinde özellikle 3 konu üzerinde durmaktadırlar (5).…”
Section: Discussionunclassified
“…In this study, medical errors in surgical departments and in gynecological and obstetric departments were found to occupy a significant place. According to the study done on the nurses by Alemdar and Aktaş (11), diagnostic mistakes are the second most important cause of medical errors. Giraldo et al (12) found that 25,1% of medical errors were based on diagnosis, and 22,2% were related to surgical practice in their study of court cases.…”
Section: Discussionmentioning
confidence: 99%